Ética e técnica na pós-história. Uma inserção no pensamento de Vilém Flusser - Fernandes, Alexandre Cortez (My University, 2017)
The research problem is about the possibility of submit the technical object to an ethical statute, taking into consideration the concepts of post-history and apparatus, in the terminology consecrated in Vilém Flusser's philosophy. The research method was the analytical. The relevance of the issue is to create reflexive tension about the conceptual set of Vilém Flusser, in order to compare it with the model that we live in society. It is defended the possibility of surpassing machines and, through art, allowing people to feel themselves free, capable of doing something by themselves without the use of technique, to perceive themselves as desirous human beings. The research was based on the theoretical contribution of Vilém Flusser, with references to Hans Jonas’s ethic of responsability.
O problema investigado versa sobre a possibilidade de submissão do objeto técnico a um estatuto ético, levando-se em consideração os conceitos de pós-história e de aparelho, na terminologia consagrada pela filosofia de Vilém Flusser. O método utilizado foi o analítico. A relevância do tema consiste em gerar tensão reflexiva sobre o conjunto conceitual de Vilém Flusser, com o fito de cotejá-lo com o modelo que vivemos em sociedade. Propugna-se ser possível ultrapassar as máquinas e, via a arte, permitir com que as pessoas se apreendam livres, capazes de fazer algo sozinhas, sem o uso da técnica, para se perceberem como seres humanos desejosos. A pesquisa se baseou no aporte teórico de Vilém Flusser com remissões à ética da responsabilidade de Hans Jonas.
Keywords: Ética; História - Filosofia; Ethics; History - Philosophy; Flusser, Vilém, 1920-1991 - Crítica e interpretação